Development of an IMU-based foot-ground contact detection (FGCD) algorithm. Issue 3 (4th March 2017) - Kim, Myeongkyu; Lee, Donghun
Abstract: It is well known that, to locate humans in GPS-denied environments, a lower limb kinematic solution based on Inertial Measurement Unit (IMU), force plate, and pressure insoles is essential. The force plate and pressure insole are used to detect foot-ground contacts. However, the use of multiple sensors is not desirable in most cases. This paper documents the development of an IMU-based FGCD (foot-ground contact detection) algorithm considering the variations of both walking terrain and speed. All IMU outputs showing significant changes on the moments of foot-ground contact phases are fully identified through experiments in five walking terrains. For the experiment on each walking terrain, variations of walking speeds are also examined to confirm the correlations between walking speed and the main parameters in the FGCD algorithm. As experimental results, FGCD algorithm successfully detecting four contact phases is developed, and validation of performance of the FGCD algorithm is also implemented. Practitioner Summary: In this research, it was demonstrated that the four contact phases of Heel strike (or Toe strike), Full contact, Heel off and Toe off can be independently detected regardless of the walking speed and walking terrain based on the detection criteria composed of the ranges and the rates of change of the main parameters measured from the Inertial Measurement Unit sensors.